2015
DOI: 10.5897/ijnm2014.0157
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of men about vasectomy as a method of family planning among married men working in Babcock University, Ogun state, Nigeria

Abstract: This study investigated the level of knowledge and attitude of married male workers about vasectomy and also the factors influencing the attitude of married men working in Babcock University towards vasectomy. Stratified random sampling technique was used to select 200 participants from the academic and administrative work divisions of the University and a self-constructed questionnaire was administered and 150 were retrieved and analysed using both descriptive and inferential statistics. Findings revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 9 publications
(11 reference statements)
6
17
0
1
Order By: Relevance
“…The majority (43.1%) of men were aged between 31 and 39 years, educated at the primary level (42.3%), with a Catholic affiliation (42.3%). Our predominate age range was similar to other studies in India, [12] Edo State in Nigeria, [18] and Ogun State in Nigeria, [19] when men were "in their prime." [18] In contrast, two other studies involving older men (40-49 years) in Rwanda, [20] and Nepal, [21] the men had good knowledge, positive attitude, and acceptance of vasectomy.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The majority (43.1%) of men were aged between 31 and 39 years, educated at the primary level (42.3%), with a Catholic affiliation (42.3%). Our predominate age range was similar to other studies in India, [12] Edo State in Nigeria, [18] and Ogun State in Nigeria, [19] when men were "in their prime." [18] In contrast, two other studies involving older men (40-49 years) in Rwanda, [20] and Nepal, [21] the men had good knowledge, positive attitude, and acceptance of vasectomy.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies had similar results in India [12] and Nigeria. [18,19] In Nepal, 69% of men had moderate knowledge level; however, they were more likely to be older, college graduates, and post-vasectomy. [21] The Nepal study was similar to one in Rwanda, where older men had higher knowledge scores (mean 91%) post-vasectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study revealed that the vast majority of doctors were convinced that the average Nigerian male will not accept vasectomy when indicated while more than three-fifth consider bilateral tubal ligation a more appropriate option for permanent contraception in our setting (15). The bias to believe that Nigerian males will not accept vasectomy is clearly not borne out of the experience of counselling males for vasectomy since most of the Doctors admitted to not counselling often for vasectomy (15,16,17).…”
Section: Discussionmentioning
confidence: 99%